BLENDED LEARNING: A STRATEGIC APPROACH TO BRIDGE THE DIGITAL DIVIDE - Khriam, Vanessa Vera; Rymbai, Rihunlang (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Incorporating digital technology in education has profoundly altered learning methodologies, resulting in the emergence of blended learning— the synthesis of online and in-person instruction. The proliferation of ICT infrastructure has enabled flexible, high-quality learning experiences, promoting educational inclusivity. The digital divide obstructs equitable access to education, especially in underserved and marginalized communities. Rural and socioeconomically disadvantaged communities face challenges in adopting digital learning due to insufficient internet connectivity and limited resources. Blended learning is a strategic method to address these disparities by combining digital and physical learning environments. The present research examines the capacity of blended learning to alleviate digital disparities through the utilization of flexible delivery methods, technological progress, and pedagogical innovations. While blended learning presents a viable solution to the digital divide, continued research and strategic investments are necessary to ensure long-term educational equity and effectiveness.